2015
DOI: 10.1111/jfq.12176
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cephalaria Syriaca Flour on the Quality of Sunn Pest (Eurygaster Integriceps)‐Damaged Wheat

Abstract: The effects of Cephalaria syriaca flour on the quality of sunn pest-damaged wheat were investigated. Sunn pest-damaged wheat was blended into sound wheat at different levels (5, 10 and 15%). C. syriaca flour was then added at 0.5, 1.0 and 1.5% levels. The rheological properties of sunn pest-damaged wheat flour with added C. syriaca flour were considerably improved, in particular with regard to farinograph characteristics (dough stability, mixing tolerance index [MTI] and degree of softening [DS]) and instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Extracts from various species of Cephalaria have been used in traditional medicine for many years due to their antimicrobial, antifungal, cytotoxic, antioxidant, antidiabetic and hypothermic activities [ 27 , 28 , 29 , 30 , 31 ]. These plants are used in folk medicine to cure cardiac and lung diseases, rheumatism, and regulate menstruation [ 32 , 33 ]. Moreover, they are used in veterinary medicine and agriculture, as a wool dye and as an additive to bread [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extracts from various species of Cephalaria have been used in traditional medicine for many years due to their antimicrobial, antifungal, cytotoxic, antioxidant, antidiabetic and hypothermic activities [ 27 , 28 , 29 , 30 , 31 ]. These plants are used in folk medicine to cure cardiac and lung diseases, rheumatism, and regulate menstruation [ 32 , 33 ]. Moreover, they are used in veterinary medicine and agriculture, as a wool dye and as an additive to bread [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Farinograph DDT is an essential indicator of protein quality of flour and strong flour has been reported to have a higher DDT than weaker ones (Karababa and Ozan, 1998). It is reported that the ST is a parameter indicating the flour strength, tolerance of flour to kneading and that strong flours have high ST (Basar et al, 2016).…”
Section: Effects Of Different Tempering Treatments On Farinograph Pro...mentioning
confidence: 99%
“…The rheological properties of the dough prepared from wheat flour can be evaluated by various methods such as farinograph, extensograph, mixograph and alveograph (Diósi et al, 2015;Aslan and Gul, 2016;Gul et al, 2017;Dizlek and Ozer, 2017a). The farinograph test is the essential in terms of being a basic analysis that reveals the rheological properties and bread qualities of flour during kneading (Basar et al, 2016). The most critical rheological properties of dough are often described as resistance (elasticity), strength and extensibility (EX) are determined by Extensograph (Dizlek and Ozer, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…к муке из поврежденных вредной черепашкой зерен пшеницы по данным оценки на фаринографе существенно улучшало реологические характеристики клейковины. Такая добавка традиционно используется в Турции для улучшения хлебопекарных качеств муки (Başar et al, 2016). Для восстановления вязкоэластичных свойств и газоудерживающей способности клейковины из поврежденных клопами зерен часто используют подходы, аналогичные тем, что обычно применяют для улучшения качества муки и теста, в т.ч.…”
Section: улучшители клейковины поврежденной протеазами хлебных клоповunclassified